The Cost of a Nutritious Diet in Bangladesh, Bhutan, India, and Nepal - Dizon, Felipe; Wang, Zetianyu; Mulmi, Prajula (World Bank, Washington, DC, 2021)
This paper calculates and compares the minimum cost of a recommended diet across four countries in South Asia. The analysis finds that the cost of a recommended diet is highest in the smaller countries, such as Bhutan and Nepal, but because of differences in purchasing power, more households are unable to afford the cost of a recommended diet in India. Within countries, the cost and affordability vary across urban and rural areas, subnational areas, and seasons of the year. The cost of perishable food items, such as vegetables and fruits, drives the differences across subnational areas and seasons. In a context of constrained resources, this suggests the need for strategic prioritization of investments and service improvements in transport and storage of food and, more broadly, a rethink of food policies.